ANALISIS SUMBER DAN PENGGUNAAN MODAL KERJA PADA PT. ARITA PRIMA INDONESIA Tbk TAHUN 2016-2019 - Dodi Safari; Eka Sevtia Mesta (Fakultas Ekonomi Universitas Tridinanti Palembang, 2020)
This study aims to see the working capital conditions of PT. Arita Prima Indonesia Tbk by calculating the source and use of working capital. The results of calculating the source and use of working capital at PT. Arita Prima Indonesia Tbk for the period 2016-2019, namely the development of working capital has increased by 3.39% in the 2016-2017 period and shows an excess of working capital in 2017 amounting to IDR 2,737,702,490. For the 2017-2018 period, the development of working capital increased by 28.52%, indicating an excess of working capital in 2018 amounting to Rp. 23,316,600,337. Whereas in the 2018-2019 period, the development of working capital decreased by 0.19%, indicating a shortage of working capital in 2019 amounting to Rp.204,079,037. The use of working capital at PT. Arita Prima Indonesia Tbk for the 2016-2019 period, namely the use of working capital in the 2016-2017 period is appropriate because in the operational management of PT. Arita Prima Indonesia Tbk has excess working capital of Rp. 2,737,702,490. The use of working capital in the 2017-2018 period is appropriate because in the operational management of PT. Arita Prima Indonesia Tbk, there is an excess of working capital of Rp. 23,316,600,337. Meanwhile, the use of working capital in the 2018-2019 period is not appropriate because in the operational management of PT. Arita Prima Indonesia Tbk, there is a working capital deficiency of Rp. 204,079,037. Keywords:Working Capital, Sources and Use of Working Capital